Pertanggungjawaban Pidana terhadap Penyertaan Anak Sebagai Pelaku Tindak Pidana: Studi Putusan Nomor 22/PID/SUS.ANAK/2016/PN JKT.TIM - Muhammad Keysha Yogi Armanda; Frans Simangunsong (Media Hukum Indonesia (MHI), 2026)
The phenomenon of children’s involvement in terrorism cases presents challenges for national law enforcement and raises debate regarding the appropriate form of criminal liability, particularly when such involvement is influenced by adults within terrorist networks. This study analyzes the criminal liability of Children based on the degree of their participation in terrorism cases. This research employs a normative juridical method by examining positive legal provisions, legal concepts, legislation, and court decisions relevant to the research problem. The findings show that, in Decision Number 22/Pid.Sus.Anak/2016/PN Jkt.Tim, the Child was qualified as an accomplice because his role was limited to the preparation of explosive materials. Although Article 15 of Law Number 5 of 2018 places accomplices and principal offenders under the same criminal sanctions, the determination of criminal liability for Children must still consider the degree of involvement, the characteristics of the Child, the best interests of the Child, and the objectives of guidance and rehabilitation in accordance with the principle of individualized sentencing.